Si-DLC coating on the surface of the hip endoprosthesis - Jędrzej Płocki; Ireneusz Kotela; Agnieszka Bejer; Piotr Niedzielski; Adam K. Puszkarz; Andrzej Kotela (Studia Medyczne)
Current challenges regarding improving the materials used for implant production focus on improving mechanical strength, biocompatibility, bioactivity, and resistance to wear related to longer periods of prostheses use. The Polish company MEDGAL has patented a new type of bone implant coatings covered with a Si-DLC (silicon-carbon) layer. It is characterised by a carbon layer with a silicon fraction of +3/+5%. The process of chemical vapour deposition assisted by high-frequency plasma RF PACVD was used for production. The advantages of the method used are low process temperatures that do not cause structural changes, and thus there is no risk of intergranular corrosion. Carbon and carbon-silicon layers of high purity and homogeneity were obtained. Thanks to the use of a silicon particle, the proliferation of osteoblasts is stimulated. Silicon is also responsible for the increase in the expression of genes that stimulate the formation of ossification thanks to GMP-2 and may affect the stimulation of type I collagen synthesis.